Peran Kepemimpinan Sebagai Pendorong Prestasi Kerja Pegawai Kantor Kementerian Agama Kabupaten Lumajang - Muhammad Mudhofar; Tatang Gumanti (Universitas Muhammadiyah Jember, 2018)
ABSTRACT The success of the organization in realizing the desired goals and the ability to fulfill its social rights and responsibilities is closely related to the managerial ability of a leader. Organizational goals are easier to achieve if the leader in carrying out his duties and functions goes well. Effective leadership is very necessary in the organization, including the ability to move and influence the behavior of individuals and groups within the organization. A good leadership style is expected to encourage more competitive organizations including the ability to empower all the potential that exists in the organization to improve employees’ work achievement, performance allowance and work motivation. This research was carried out on employees in the Ministry of Religion Affair (MRA) in the district of Lumajang with the aim to test and analyze the influence of leadership as a driver of employee employees’ work achievement and increase performance allowance and work motivation. The results of hypothesis testing with Structural Equation Modeling (SEM) analysis tools show that effective leadership will be a direct driving factor in employees’ work achievement and indirectly affect the increase in performance allowance and work motivation.Keywords: leadership, performance allowance, motivation, employees’ work achievement.